THE EFFECT OF SERVICESCAPE ON IMPULSE BUYING (A Case Study Ever on Brawijaya University Students Having Purchased at Sardo Supermarket ) - SYAFAAT, MUHAMMAD ARIEF (Jurnal Ilmiah Mahasiswa FEB, 2017)
Impulse buying, better known as unplanned (spontaneous) purchase, is the act of buyers without the desire or intention to purchase before entering the store. This study aims at determining the effect of Impulse buying variables, consisting of ambient condition, spatial layout & functionality, and signs, symbols, and artefacts. This study is conducted on students of Brawijaya University Students Having Purchased at Sardo Supermarket.The population of the study is students of Brawijaya University Students Having Purchased at Sardo Supermarket. This study uses 259 samples selected through purposive sampling. The analysis uses multiple linear regression in SPSS.The results show that Ambient Condition is significantly positive to impulse buying at 0,001. Spatial layout and functionality is significantly positive to impulse buying at 0,000. Signs, symbols, and artefacts is significantly positive to impulse buying at 0.015.Keywords: ambient condition, spatial layout and functionality, signs, symbols, and artefacts, impulse buying